New camerate crinoid genera from the Upper Ordovician (Katian) of Estonia: evolutionary origin of family Opsiocrinidae and a phylogenetic assessment of Ordovician Monobathrida. (3rd April 2019) - Cole, Selina R.; Toom, Ursula
Abstract : Most major crinoid clades first appear in the fossil record during the Ordovician, but the evolutionary origins of many higher taxa remain unresolved. Here, the first camerate crinoids from the Katian (Upper Ordovician) of Estonia with complete calyces are described. Phylogenetic analyses are conducted to determine the affinities of two new genera and to assess the evolutionary origins of the families Opsiocrinidae (Diplobathrida) and Glyptocrinidae (Monobathrida). Sakucrinus krossi gen. et sp. nov. is identified as the earliest known member of Opsiocrinidae and demonstrates that: (1) the family originated much earlier than was previously assumed; (2) features previously considered plesiomorphic for the family are instead derived; and (3) the family is likely closely related to the Dimerocrinitidae. Family Pachycephalocrinidae fam. nov. is established to accept the monocyclic glyptocrinid Pachycephalocrinus jaanussoni gen. et sp. nov. Pachycephalocrinus jaanussoni displays morphological features that are unique among monobathrid crinoids, including a large periproct in the calyx side. Inclusion of Pachycephalocrinus in the first phylogenetic analysis focusing on Ordovician monobathrid crinoids elucidates evolutionary relationships among Ordovician monobathrids and calls into question the validity of superorder Compsocrinina. The new genera described here provide important insight into the timing of origination and morphological diversity of higher taxa during the early evolutionary history of camerate crinoids. http://zoobank.org/urn:lsid:zoobank.org:pub/28B337ED-1008-40CD-8B86-51DAD81B45F6